Impact of customer-oriented strategy on financial performance with mediating role of HRM and innovation capability. Issue 3 (1st April 2019) - Chaudhry, Naveed Iqbal; Aftab, Iqra; Arif, Zainab; Tariq, Usman; Roomi, Muhammad Azam
Abstract : Purpose: The purpose of this paper is to explain the relationship between customer-oriented strategy (COS) and financial performance (FP) of firm, to examine the role of supportive human resource management (HRM) in COS implementation and contribution toward FP of firm. It also examines the mediating role of innovation capability (IC) between COS and FP of firm. Design/methodology/approach: The approach used for this study is quantitative. Data required for testing of hypothesis were gathered from the managers of manufacturing firms of Gujranwala, Pakistan. To conduct the data analysis, structural equation modeling was used. Findings: Findings of this study showed that there is significantly positive relation between COS and FP with the significant positive mediating effects of supportive HRM and IC. Research limitations/implications: This research has been conducted in manufacturing sector only. So, it is suggested to future researchers to carry out this research in other sectors. Second, this research focused only on IC but there are many other organizational capabilities (OC) that can be used. Practical implications: This research would be helpful for all firms adopting COS to understand that how to mobilize their HR to accomplish the purpose of strategy. It will enable manufacturing firms to understand and work on IC. Originality/value: This study is anticipated to add value to the existing literature of strategy process and OC. This study is one of the first to examine IC as mediator between COS and organizational FP so it opens new areas for research.